Making small-dams work: everyday politics around irrigation cooperatives in Turkey. - Selin Le Visage (European Journal of Turkish Studies)
Much research on environmental issues in Turkey has focused on conflictual state-led projects, for example on the large-scale GAP irrigation schemes or hydroelectric plants. This article shows that, in a complementary way, it is also necessary to study less contested projects, since power struggles for control over natural resources tend to occur in the implementation and everyday management of these as well. It analyses the everyday dynamics of negotiations and the arrangements found locally during the implementation of the national programme ‘1000 gölet in 1000 days’. Gölet, hillside reservoirs built for irrigation, enabled the government to demonstrate its involvement at a very local level in numerous villages in Turkey. However, the complex implementation of these numerous and relatively small projects compelled agents of the hydraulic administration to negotiate the transfer of their management to local actors. Taking irrigation cooperatives in the Izmir region as a starting point, this article highlights how the shaping of social arrangements for managing the new water resource depends both on local and supralocal power relations. It challenges the idea of a monolithic state disconnected from homogenous communities of irrigators, and reveals the flexibility of these relations. It focuses on the way actors – not only irrigators but also state officials at the local level – adapt norms, bend rules and find arrangements in order to shape new water institutions and infrastructure.